Geschichtsschreibung und Täufertum: Reformatorische Vielfalt als narrative Herausforderung 1672-1848 - Schmidt, Steffie (Beiträge zur historischen Theologie, 2025)
Integrating the Anabaptist movement coherently into their own historiographical concept of the Reformation challenged both Lutheran and Reformed scholars. Steffie Schmidt examines the extent to which these narrative patterns were questioned and possibly updated under the conditions of pietism and Enlightenment.